Chemical Morphing of DNA Containing Four Noncanonical Bases. Issue 26 (9th May 2016) - Eremeeva, Elena; Abramov, Michail; Margamuljana, Lia; Rozenski, Jef; Pezo, Valerie; Marlière, Philippe; Herdewijn, Piet
Abstract: The ability of alternative nucleic acids, in which all four nucleobases are substituted, to replicate in vitro and to serve as genetic templates in vivo was evaluated. A nucleotide triphosphate set of 5‐chloro‐2′‐deoxyuridine, 7‐deaza‐2′‐deoxyadenosine, 5‐fluoro‐2′‐deoxycytidine, and 7‐deaza‐2′deoxyguanosine successfully underwent polymerase chain reaction (PCR) amplification using templates of different lengths (57 or 525mer) and Taq or Vent ( exo ‐) DNA polymerases as catalysts. Furthermore, a fully morphed gene encoding a dihydrofolate reductase was generated by PCR using these fully substituted nucleotides and was shown to transform and confer trimethoprim resistance to E. coli . These results demonstrated that fully modified templates were accurately read by the bacterial replication machinery and provide the first example of a long fully modified DNA molecule being functional in vivo. Abstract : Chemically redesigned DNA, in which all four nucleobases are functionalized (denoted DZA), was used to transfer genetic information in living organisms. Using a gene encoding resistance to the antibiotic trimethoprim, a fully morphed DNA was successfully replicated in vitro and served as a genetic template in vivo.